2010
DOI: 10.3899/jrheum.091250
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Arthritis and Other Musculoskeletal Sequelae Following an Outbreak of Salmonella hadar in Castellon, Spain

Abstract: The incidence of ReA and musculoskeletal symptoms after the infection was high. The use of antibiotics for S. hadar infection offered some protection against musculoskeletal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Of these studies, increased risk of ReA development was observed following treatment of infection with antibiotics (class not provided) for Campylobacter and fluoroquinolones for NTS infection ( n  = 1 and 2, respectively) (Locht and Krogfelt, 2002, Dworkin et al, 2001, Mattila et al, 1998). Three studies found a protective effect in the use of antibiotics for NTS; however the findings were not statistically significant (Arnedo-Pena et al, 2010, Buxton et al, 2002, Hannu et al, 2002b). The remaining study did not find any associated risk with antibiotic usage for either Campylobacter or NTS infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these studies, increased risk of ReA development was observed following treatment of infection with antibiotics (class not provided) for Campylobacter and fluoroquinolones for NTS infection ( n  = 1 and 2, respectively) (Locht and Krogfelt, 2002, Dworkin et al, 2001, Mattila et al, 1998). Three studies found a protective effect in the use of antibiotics for NTS; however the findings were not statistically significant (Arnedo-Pena et al, 2010, Buxton et al, 2002, Hannu et al, 2002b). The remaining study did not find any associated risk with antibiotic usage for either Campylobacter or NTS infection.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported ReA following Campylobacter ( n  = 19) and NTS infections ( n  = 26) (Buxton et al, 2002, Bremell et al, 1991, Dworkin et al, 2001, Eastmond, 1983, Ekman et al, 2000, Gumpel et al, 1981, Hakansson et al, 1976, Hannu et al, 2002a, Hannu et al, 2002b, Helms et al, 2006, Pitkanen et al, 1981, Lee et al, 2005, Locht et al, 1993, Locht and Krogfelt, 2002, Locht et al, 2002, Mattila et al, 1994, Mattila et al, 1998, McColl et al, 2000, Petersen et al, 1996, Pitkanen et al, 1983, Ponka et al, 1984, Rohekar et al, 2008, Rudwaleit et al, 2001, Samuel et al, 1995, Schiellerup et al, 2008, Schoenberg-Norio et al, 2010, Short et al, 1982, Ternhag et al, 2008, Thomson et al, 1992, Thomson et al, 1994, Townes et al, 2008a, Tuompo et al, 2013, Uotila et al, 2014, Urfer et al, 2000, Doorduyn et al, 2008, Arnedo-Pena et al, 2010, Eastmond et al, 1983, Melby et al, 1990) in up to 63% of patients with either infection (Supplementary Table 4). The majority of studies reported ReA triggered by Campylobacter ( n  = 14) or NTS infection ( n  = 18) in < 10% of patients with gastroenteritis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In rare cases, infections can cause large-volume watery diarrhea, or they may be associated with tenesmus. Risk factors associated with the development of ReA include signs of disease severity, duration of diarrhea, and weight loss [114]. Serology tests include the Widal agglutination test, hemagglutination tests, and countercurrent immunoelectrophoresis tests.…”
Section: Salmonellamentioning
confidence: 99%